(untitled) (Texas Journal of Medical Science, 2023)
Background: Emergencies are sudden serious events requiring immediate action to avert grave consequences. In our life when we see or hear word emergency always our mind go to how prevent and manage such events and methods of decreasing degree of morbidity and mortality. Aim of the study: To assess the prevalence of emergency ENT and their management, to obtain base line data for subsequent studies and to prepare our self and our department for dealing with most common ENT emergencies and availability of proper instruments and equipment . Patients & methods: prospective study (data base study) conducted at Ghazi Al-Harirry hospital in the department of Otolaryngology for one year duration from (the first of July 2016 to the end of June 2017). One thousand patients that were included in the study and the patients were classified to five groups according to medical city ENT triage to facilitate their management. Results: The current study was included one thousand patients, (26.5%) of them were suffer from foreign bodies in the throat, epistaxis represent [(190 cases) 182(18.2%) of the patients have anterior epistaxis, and only 8 (0.8%) was posterior epistaxis], 175(17.5%) foreign bodies in nose and 125(12.5%) foreign bodies in ear stridor is found in 115(11.5%), quinsy in 26(2.6%) of patients and 25(2.5%) have fracture nose Conclusions: The green group of the patients were the most common emergencies in the current study and the most common emergency in this group was the fish bones foreign bodies in throat. Followed by yellow group and the anterior epistaxis the commonest among them. The next white, red and black.